Transforming Growth Factor Î²1 and Tropoelastin Expression in Uterine Prolapse - Alvilusia Alvilusia; Amir Fauzi; Azhari Azhari; Wresnindyatsih Wresnindyatsih; Irsan Saleh (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the correlation of the expression of transforming growth factor beta (TGF-Î²1) and tropoelastin in uterine prolapse. Method: A cross-sectional study of 30 subjects suffered from uterine prolapse in the Department of Obstetrics and Gynecology Dr. Mohammad Hoesin hospital Palembang. The study was conducted since December 1st, 2014 until July 31st, 2015. The sample was from the sacrouterine ligament and immunohistochemical examination was conducted to see the expression of TGF-Î²1 and tropoelastin. Result: Of the 30 subjects obtained, the expression of TGF-Î²1 was on 30 subjects consisting of 18 (60%) for weak expression and 12 (40%) for strong expression. Meanwhile, the strong tropoelastin expression was on 18 subjects (60%) and weak tropoelastin expression on 12 subjects (40%). There was a positive correlation between TGF-Î²1 and tropoelastin expression with moderate correlation (p=0.014; r=0.44). Conclusion: There is a positive correlation between the TGF-Î²1 and tropoelastin expression of sacrouterine ligament in uterine prolapse with moderate correlation. [Indones J Obstet Gynecol 2016; 4-2: 70-74] Keywords: transforming Growth Factor Beta 1, tropoelastin, uterine prolapse